Highly enhanced photoelectrocatalytic properties by α-Fe2O3 modified NF-TiO2 pyramids with dominant (101) facets. (20th October 2016) - Wang, Qi; Zhu, Naxin; Liu, Enqin; Fu, Leiling; Zhou, Tiantian; Cong, Yanqing
Graphical abstract: Highlights: Pyramid-shaped NF-TiO2 was formed via calcining TiO2 -NTs with NH4 F. α-Fe2 O3 was deposited on dominant (101) facets of NF-TiO2 . Easier generation, separation and transfer of e − -h + pairs were attained. Significant synergies appeared in simultaneous PEC removal of Cr(VI) and phenol. k Cr(VI) and k phenol increased by 4.3 and 3.6 times relative to Fe2 O3 /TiO2 -NTs. Abstract: Visible-light-active Fe2 O3 /NF-TiO2 film was prepared by depositing α-Fe2 O3 nanoparticles onto the surface of pyramid-shaped NF-TiO2 via sequential electro-deposition and electro-anodization processes. NF-TiO2 with dominant (101) facets was obtained via calcining TiO2 nanotubes (TiO2 -NTs) in the presence of NH4 F. The structural and optical properties were carefully studied by XRD, SEM, HRTEM, XPS and UV-Vis-DRS. Photoelectrochemical measurements, such as linear sweep voltammetry (LSV), electrochemical impedance spectroscopy (EIS) and Mott-Schottky (M-S) plots, were also carried out to investigate the generation, separation and transfer of photogenerated charges. It was found that Fe2 O3 /NF-TiO2 exhibited the best photoelectrocatalytic (PEC) activity relative to Fe2 O3 /TiO2 -NTs or Fe2 O3 /N-TiO2 . The formation of anatase-rutile heterojunction, wider spectral response, increased photocurrent response and greatly reduced charge transfer resistance, could be positive driving force for the enhanced PEC activity. Simultaneous PEC reduction of Cr(VI) and degradation of phenol were evaluated under visible light using Fe2 O3 /NF-TiO2 film as photoanode and Ti sheet as cathode. The calculated rate constants for Cr(VI) and phenol were 4.3 and 3.6 times relative to that on Fe2 O3 /TiO2 -NTs, respectively. Good stability was also confirmed in cyclic runs using the optimized photoanode.